채널 정렬을 활용한 D2D 캐싱 네트워크용 전송 기법 - 정무웅(Moo-Woong Jeong); 류종열(Jong Yeol Ryu); 김성환(Seong Hwan Kim); 이웅섭(Woongsup Lee); 반태원(Tae-Won Ban) (한국정보통신학회논문지, 2018)
Mobile Device-to-Device (D2D) caching networks can transmit multimedia data to users directly without passing through any network infrastructure by storing popular multimedia contents in advance that are popular among many mobile users at caching server devices (CSDs) in distributed manners. Thus, mobile D2D caching networks can significantly reduce backhaul traffic in wired networks and service latency time of mobile users. In this paper, we propose an efficient transmission scheme that can enhance the transmission efficiency of mobile D2D caching networks by using multiple CSDs that are caching the contents that are popular among mobile users. By sorting the multiple CSDs that are caching a content that mobile users want to receive according to their channel gains, the proposed scheme can reduce the complexity of algorithm significantly, compared to an optimal scheme based on Brute-force searching, and can also obtain much higher network transmission efficiency than the existing Blanket and Opportunistic transmission schemes. 모바일 Device-to-Device(D2D) 캐싱 네트워크는 다수의 모바일 사용자들 사이에서 인기 있는 멀티미디어 콘텐츠들을 사전에 캐싱 서버 단말 (CSD: Caching Server Device)들에 분산 저장한 후 네트워크 인프라를 거치지 않고 사용자들에게 직접 데이터를 전송할 수 있다. 이를 통해서 유선 트래픽과 서비스 지연 시간을 획기적으로 줄일 수 있다. 본 논문에서는 이러한 모바일 D2D 캐싱 네트워크에서 모바일 사용자가 요구하는 콘텐츠를 캐싱하고 있는 다수의 CSD들을 활용하여 네트워크의 전송 효율을 높일 수 있는 효율적인 전송 기법을 제안한다. 제안된 기법은 각 모바일 사용자가 전송 받기를 희망하는 콘텐츠를 캐싱하고 있는 다수의 CSD들을 채널 이득에 따라서 정렬하여 최적의 CSD 조합을 선택함으로써 기존의 Brute-force 탐색 기반의 최적 방식 대비 복잡도를 획기적으로 줄일 수 있으며, Blanket 전송 방식과 Opportunistic 전송 방식 대비 높은 네트워크 전송 효율을 얻을 수 있다.